OPINIÃO DE CRIANÇAS SOBRE O LAR DE LONGA PERMANÊNCIA PARA IDOSOS: MUDANÇAS POR CONTATO LÚDICO - Ultramari, Samantha Ribeiro (2007)
This research verifies through drawing the children’s opinion on the Long Stay Home for the Elderly, before and after ludic contact with the resident elderly. So as to better characterize the elderly population, a neuropsychological profile is outlined. This work was developed with 21 resident elderly and 61 children aged between 7 and 12, from public Primary and Secondary schools. It begins with verification trough drawing of the children’s opinion on Home for the Elderly. Then a ludic intervention with the participation of children and the elderly takes place: there are 10 encounters with symbolic games and rule games. Afterwards, the children’s opinion is re-evaluated and a neuropsychological evaluation of the elderly is done, making use of the Mini Mental State Exam, of the Scale of Geriatric Depression, of the Short-Form Health Survey (SF-36) and of the Katz Rate. In order to verify the children’s opinion expressed through drawing, the open title “Home for the Elderly is…” is suggested to be completed. The drawings are analysed based on the projective, based on the projective House-Tree-Person (HTP) test. The results show that from one application of the test to the other there was a change in the opinion of 67% of the children, manifested a more positive opinion, perceiving the elderly as more interactive and the Home for Elderly as more humanised, as expressed in more colourful drawings of houses with doors and windows, people smiling and moving, and affectionate messages. The negative aspects found consist of an increased number of bars and people drawn faceless, which way 0,19, on a scale of 0 to 1, on which the maximum positive value is 1. On the neuropsychological evaluation of the elderly, during MMSE, 50% have showed cognitive preservation. The other instruments indicate that most of the subjects present no depressive symptoms, emit positive opinions on their on health, take part of ludic activities and are dependant. This study, however, points out that the particularities of the researched institution, together with the realization of ludic activities, may have favoured the changes on children’s opinions after their contact with the home for the elderly. The study indicates the need of new research on the interaction of children and elderly people resident at nursing homes